Southern Patagonian iguanid lizards of the Liolaemus kingi group - Cei, José Miguel Alfredo María (1975)
Liolaemus kingi (Bell) from the eastern and central lowlands and tablelands of Argentine Patagonia, L. archeforus archeforus Donoso-Barros and Cei from the Lake Buenos Aires area, and L. archeforus sarmientoi Donoso-Barros from southern Santa Cruz province and neighboring Chilean territories, form a natural group, which is analyzed here. Serological relationships of the complex and the geographical distribution of its members are discussed.